ANALISIS NILAI TAMBAH KACANG TANAH PADA USAHA KACANG BAWANG â€œMARINDIâ€ DI KOTA MANADO (ANALYZING THE VALUES ADDED OF THE PEANUTS ON ONION BEAN BUSINESS â€œMARINDIâ€ IN MANADO CITY) - Clerensia L. Tololiu; Grace A.J. Rumagit; Joachim N.K. Dumais (AGRI-SOSIOEKONOMI, 2021)
The objective of this research is to determine the added value of the peanut processing beans onion bean business in Manado City. This research was conducted from January 2020 to February 2020. The data used in this study are primary data obtained from direct interviews with business owner and employers in â€œMarindiâ€ onion bean business. The data analysis used calculation of cost, revenue and added value from beans into onion beans. The research result showed that by using 1 kg of beans aan raw material, the onion bean business produces added value Rp. 58. 467,00.